Simple Cocasting Method to Prepare Magnetic Mesoporous FePt/C Composites and Their Protein Adsorption Property - Yufang Zhu; Xing He (Journal of Chemistry)
A simple cocasting method has been developed to prepare magnetic mesoporous FePt/C composites with superparamagnetic FePt nanoparticles embedded in carbon walls. Furfuryl alcohol, iron(III) acetylacetonate (Fe(acac)3), and platinum(II) acetylacetonate (Pt(acac)2) were used as the carbon and FePt nanoparticle precursors to be simultaneously incorporated into the channels of mesoporous silica SBA-15 template by the incipient wetness impregnation technique. After the polymerization of furfuryl alcohol, the carbonization in argon, and the removal of silica template, magnetic mesoporous FePt/C composites were finally obtained. Magnetic mesoporous FePt/C composites have high surface area of 1244 m2/g and narrow mesopore size distribution peaked at 4.93 nm. FePt nanoparticles were well embedded in mesoporous carbon walls, and mesoporous FePt/C composites exhibit superparamagnetic behavior. Using cytochrome c (Cyt c), myoglobin (Mb), and bovine serum albumin (BSA) as model proteins, the adsorption capacities of Cyt c, Mb, and BSA on magnetic mesoporous FePt/C composites can reach ca. 200, 162, and 121 μg/mg, respectively. These results indicated that mesoporous FePt/C composites have potential as magnetically separable adsorbent for biomolecules separation.